2019
DOI: 10.1002/adom.201801368
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality Controlling of Cs3Sb2I9 for Efficient All‐Inorganic Planar Thin Film Solar Cells by HCl‐Assisted Solution Method

Abstract: sensitivity are the bottlenecks in future commercialization applications. [4,5] Fully-inorganic lead halide perovskites (APbX 3 , A = Cs, Rb, K, etc.), without the organic part affection were expected to resolve the problem of stability. [4,6,7] According to the work of Kubelk et al., fullyinorganic perovskites have similar bandgaps to organo-lead halide analogs and hold much better thermal stability. [4,[7][8][9] Under the scenario of lead-free perovskite, tin (Sn) and germanium (Ge) elements have been consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
91
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 36 publications
2
91
0
Order By: Relevance
“…The black part of the curves at lower bias voltage is an ohmic response, the colored portions in the center are trap-filled limited regimes (V TFL ), and a trap-free SCLC regime at high voltage. [36] The onset voltage of trap-filled limit and trap density are linked according to the following equation…”
Section: Resultsmentioning
confidence: 99%
“…The black part of the curves at lower bias voltage is an ohmic response, the colored portions in the center are trap-filled limited regimes (V TFL ), and a trap-free SCLC regime at high voltage. [36] The onset voltage of trap-filled limit and trap density are linked according to the following equation…”
Section: Resultsmentioning
confidence: 99%
“…[ 28 ] The same year, Umar et al demonstrated enhanced photovoltaic performance in Cs 3 Sb 2 I 9 using intermediate coordination of Cl ions to form the 2D phase at 160 °C, yet, no Cl − remained in the final film. [ 29 ] Very recently, Peng and co‐workers experimentally verified Jiang's predictions with Cs + at the A‐site; they indeed observed a transition from 0D to 2D at low solution processing temperatures (135 °C) by tuning the initial ratios of I‐ and Cl‐containing precursors and have achieved a PCE of 2.15% for n‐i‐p architecture. [ 30 ] In that work, the Cs 3 Sb 2 Cl x I 9 – x films showed superior photovoltaic properties over pure Cs 3 Sb 2 I 9 , yet, over a variety of substructures, leaving the intrinsic optoelectronic role of Cl − at the X‐site unclear.…”
Section: Introductionmentioning
confidence: 91%
“…Lead halide perovskites with strong optical absorption and high carrier mobility have attracted extensive research interest as an excellent light absorber in perovskite solar cells (PSCs) . Although the defects at the film surface and grain boundaries of the perovskite layer inevitably lead to charge recombination and efficiency loss, a lot of effort has been devoted to defect passivation of the perovskite layer, achieving efficiency enhancement .…”
Section: Introductionmentioning
confidence: 99%